PPS-1 (New Delhi, 2024)
"Drishti IAS: Your Gateway to Success in Competitive Exams. In-Depth Coverage of Indian Penal Code (IPC): Thorough coverage of the Indian Penal Code (IPC), providing a comprehensive understanding of the legal provisions and principles. Essential for aspirants preparing for the Preliminary stage of judiciary exams. Updated Content for 2023: The book is designed to include the latest amendments and changes in the Indian Penal Code up to the year 2023. Stay current with the most recent legal developments relevant to the judiciary exams. Preliminary Exam-Oriented Content: Aligned with the exam pattern and requirements of Preliminary exams for the judiciary. Ensures aspirants are well-prepared for the specific demands of the legal provisions covered in the IPC. Language Accessibility: Presented in Hindi, catering to the preferences of Hindi-speaking aspirants. Facilitates a smooth learning experience for those preparing for judiciary exams in Hindi.
English
Keywords: Bharathiya Nyaya Sanhita; Indian Penal Code; Judiciary Exams; Law